2015
DOI: 10.5194/acp-15-12029-2015
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of biogenic volatile organic compounds and subsequent formation of secondary organic aerosols in a <I>Larix kaempferi</I> forest

Abstract: Abstract. We conducted simultaneous measurements of concentrations and above-canopy fluxes of isoprene and α-pinene, along with their oxidation products in aerosols in a Larix kaempferi (Japanese larch) forest in summer 2012. Vertical profiles of isoprene showed the maximum concentration near the forest floor with a peak around noon, whereas oxidation products of isoprene, i.e., methacrolein (MACR) and methyl vinyl ketone (MVK), showed higher concentrations near the canopy level of the forest. The vertical pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…It is noteworthy that the major source of NO 2 is vehicular exhaust (Kendrick et al, 2015); however, coal combustion can also emit NO x into the atmosphere (Chang et al, 2018). Previous studies have also reported that NO x could affect SOA formation (Kanakidou et al, 2005;Mochizuki et al, 2015). Moreover, PAHs, hopanes and steranes showed another episode on 23 and 24 December 2014, most likely due to a coal combustion event.…”
Section: Diurnal Variations and Meteorological Conditionsmentioning
confidence: 99%
“…It is noteworthy that the major source of NO 2 is vehicular exhaust (Kendrick et al, 2015); however, coal combustion can also emit NO x into the atmosphere (Chang et al, 2018). Previous studies have also reported that NO x could affect SOA formation (Kanakidou et al, 2005;Mochizuki et al, 2015). Moreover, PAHs, hopanes and steranes showed another episode on 23 and 24 December 2014, most likely due to a coal combustion event.…”
Section: Diurnal Variations and Meteorological Conditionsmentioning
confidence: 99%
“…Plant-emitted biogenic volatile organic compounds (BVOCs) have been extensively studied and the regional and global estimates of plant BVOC emissions are used as key drivers for atmospheric chemistry models to study the impacts of terrestrial BVOCs on the climate system . Soil-related BVOC emissions could also contribute to ecosystem emissions and thereby impact atmospheric chemistry (Kramshøj et al, 2016;Mochizuki et al, 2015;Nölscher et al, 2016), but they have been less well studied than plant emissions. BVOCs can be released through microbial decomposition of plant residues or soil organic carbon (SOC; Aaltonen et al, 2013;Insam & Seewald, 2010;Leff & Fierer, 2008;Stahl & Parkin, 1996), evaporation of litter-stored BVOCs (Aaltonen et al, 2011) and other physical processes (e.g., desorption from leaf litter tissue (Warneke et al, 1999) and from soil organic matter (Bachy et al, 2018;Schade & Custer, 2004)).…”
Section: Introductionmentioning
confidence: 99%
“…Various observational methods have been applied to explore PBAPs and SOA in natural environment both qualitatively and quantitatively. Applications of ultraviolet aerodynamic particle sizers and wideband integrated bioaerosol sensor based on fluorescence provided much information on the abundances and size distributions of PBAP Pöhlker et al, 2012). In situ observations of SOA are frequently conducted using an aerosol mass spectrometer (AMS) (Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Progress is achieved in boreal forest (Kourtchev et al, 2008) and the Amazon (Graham et al, 2003). However, few studies focused on the midlatitudinal forest with high time resolution (Miyazaki et al, 2012;Mochizuki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%